1984
DOI: 10.1017/s0141347300010806
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Programmed Instruction with Operant Training in the Language Rehabilitation of Severely Aphasic Patients

Abstract: The effectiveness of programmed instruction with operant training (P.I.O.T.) in the language rehabilitation of severe aphasics was evaluated by comparison with an attention-placebo control treatment (A.P.C.) in which non-verbal tasks were administered. Patients were divided into two groups and received first either 4 weeks of P.I.O.T. or of the A.P.C. condition. Both groups then received 4 weeks of the alternative treatment. Both groups also received some speech therapy throughout. Only two out of 24 assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The uncontrolled study of Gloning et al (1976) found a positive effect of speech therapy; the uncontrolled study of Lincoln et af. (1982) and their controlled study (Lincoln & Pickersgill, 1984;Lincoln et al 1984) found no such effect.…”
Section: A Genetic Model Of Language Dominance and Aphasia: Discussionmentioning
confidence: 89%
“…The uncontrolled study of Gloning et al (1976) found a positive effect of speech therapy; the uncontrolled study of Lincoln et af. (1982) and their controlled study (Lincoln & Pickersgill, 1984;Lincoln et al 1984) found no such effect.…”
Section: A Genetic Model Of Language Dominance and Aphasia: Discussionmentioning
confidence: 89%
“…26,27 In terms of clinical outcomes, the evidence is mixed. 24,25,28,29 Cognitive theories that explain learning according to an information-processing paradigm provide a rationale for PI. Three elements of PI are relevant: segmentation, testing, and feedback.…”
mentioning
confidence: 99%